Research progress on matrix and mechanical properties of metal matrix composite foam materials - XU Lei; SUN Shaoxiang; LI Changyun; TANG Ling; GAO Qi (Fenmo yejin jishu)
Metal matrix syntactic foams (MMSFs) are the new type of porous composite materials composed of hollow microsphere and metal matrix. The research progress on aluminum-based, magnesium-based, and steel-based composite foams in recent years was summarized in this paper, and the influence of the matrix materials and preparation processes on the microstructure and mechanical properties of metal matrix composite foams was studied. The results show that the matrix materials are the important components of the metal matrix composite foams which directly affect the structure and performance. Aluminum and its alloys have the characteristics of low density, high strength, and good plasticity, which are widely used as the matrix materials in metal matrix composite foams. Magnesium and its alloys also have the characteristics of low density, high strength, and good ductility, which are also used as the important metal matrix materials. The compressive strength and energy absorption capacity of the steel-based composite foams are superior to those of aluminum and magnesium-based composite foams, showing the better deformation state during the force application process and the higher density than that of aluminum and magnesium-based composite foam materials. Using high-entropy alloys as the matrix of composite foam materials is a new research direction, which demonstrate the excellent performance. Due to the complex internal structure of high-entropy alloys, the further in-depth research on the microstructure and mechanical properties of the prepared composite foams is still required. In addition to the metal matrix materials, the filling materials, preparation processes, porosity, interfacial reactions, and post-treatment technologies show the significant impact on the structure and properties of the metal matrix composite foams.